ANALISIS POLA SEBARAN USAHA TANAMAN HIAS DI KECAMATAN TAMBANG KABUPATEN KAMPAR - FITRIA IRZA WULANDARI; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to determine the analysis of the distribution pattern of ornamental plant business in Tambang District, to determine the business components and their relation to accessibility and location. This type of research is a descriptive study with survey methods and quantitative analysis. The subjects of this study were all business owners of ornamental plants. The sampling technique used is total sampling. The results show that (1) the distribution pattern of the business has an elongated pattern, this can increase the occurrence of buying because of the ease of accessibility and strategic location because it is always passed by many people, so that the tendency to purchase spontaneously is greater (2) business owners have 1-8 labor with wages ranging from Rp.800,000-Rp.3000,000, the smallest capital used is Rp.500,000, the highest plant price is Rp.15,000,000, some business owners rent land to open businesses, and also rent ornamental plants, marketing most occur within the province while seeds are obtained from outside the island, some of which are from the island of Java, the land area ranges from ±10×28 to ±35×45 m2, the youngest business was established in 2020, the most widely used fertilizer is manure, compost, humus, urea, and beautiful fertilizer